PENERAPAN MODEL PEMBELAJARAN KREATIF UNTUK MENINGKATKAN KETERAMPILAN MEMBUAT BENDA PERMAINAN YANG DIGERAKKAN DENGAN TALI PADA SIWA KELAS V SDN 018 SENAPELAN PEKANBARU - Sri Wahyuni Sri Wahyuni; Zariul Antosa Zariul Antosa; Lazim N Lazim N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : his study was conducted due to low skills make game objects driven by a rope. From the preliminary data only 15 students are skilled of the number of students 38 students. The purpose of this research is to improve the skills of making objects game that is driven by a rope at the fifth grade students of SD Negeri 018 Senapelan. Based on the results of this research is that the activity of teachers in the first cycle of the first meeting obtained sufficient percentage of 50% category, the second meeting sisklus second with a percentage of 70.83% good category, the first meeting of the second cycle with the percentage of 91.67% is very good category, the second meeting of the cycle both with a percentage of 95.83% is very good category. In the first cycle of the first meeting of the percentage of the student activity 62.5% categorized enough, the second meeting of the first cycle with the percentage of 79.16% good category, the first meeting of the second cycle with the percentage of 83.33% is very good category, the second meeting of the second cycle with the percentage of 95, 83% very good category. It can be seen from the results of assessment of skills make game objects driven by rope on preliminary data with an average rating of 59.60 increased in the first cycle in order to obtain an average value of 66.38, an increase in the second cycle to obtain the average value -rata 76.32.Keywords : Creative Learning, Skills Making Games object Driven by rope